Millennials, Peacebuilding, and Popular Islamic Novels: Exploring Transformative Bridges for Interfaith Relations - Nurul Aula, Siti Khodijah; Ichwan, Moch Nur (UIN Sunan Kalijaga Yogyakarta, 2022)
This article explores the role of interfaith relations in Indonesian society, with a particular focus on their representation in contemporary Islamic novels. While various programs have been implemented to foster interfaith harmony, the role of literature in promoting such relationships has received less attention. This study highlights the incorporation of interfaith themes within contemporary Islamic novels, where romantic storylines are intertwined with Islamic teachings. Millennials and young people, who constitute a significant portion of the readership, find enjoyment in these narratives and ideologies. The inclusion of interfaith narratives in these novels serves as a countermeasure to the popular